Study on the diagnostic value of folic acid-targeted nano-microbubbles in breast microcarcinoma - Xue, Nianyu; Shen, Zhenyu; Xu, Zhenbin; Zhang, Shengmin (Frontiers in Oncology, 2025)
BackgroundThe prognosis of breast cancer is significantly correlated with its early detection. It is difficult to detect breast microcarcinomas less than or equal to 5 mm by imaging examination.MethodsFolic acid-targeted nanobubbles (FA-TNBs) were prepared by the thin-film hydration method. Cytotoxicity and cellular uptake assays were used to examine FA-TNBs’ biological toxicity to cells, targeting them to breast cancer cells. In addition, by constructing 4T1 tumor mouse models and evaluating the targeting and imaging effects of FA-TNBs.ResultsThe average particle size of the fabricated FA-TNBs was 244 ± 21 nm. In vitro, cell uptake experiments showed that breast cancer 4T1 cells take up more FA-TNBs than non-targeted nanobubbles (N-TNBs) (p < 0.001). In the cytotoxicity experiment, the survival rate of 4T1 cells under each FA-TNBs concentration was over 90%. In vivo, imaging of the mouse 4T1 tumor model showed that compared with the N-TNBs group, the FA-TNBs group took a shorter time to peak (20 s, 40 s, p < 0.05), had a higher peak intensity (38.3 ± 1.5 dB, 31.7 ± 1.5 dB, p < 0.05), and the extinction time was shorter (180 s, 120 s, p < 0.05). After FA-TNB injection, there were no apparent abnormalities in the tissue sections or hematological examinations of the mice’s vital organs.ConclusionsThe prepared FA-TNBs had good water solubility, safety, biocompatibility, and enhancement of ultrasound imaging. It had an excellent imaging effect on mouse breast cancer tumors with a diameter of 5 mm and showed apparent active targeting. FA-TNBs may become a new and practical ultrasound contrast agent for the early detection of breast cancer.